Keabsahan Akta Elektronik dalam Perspektif Hukum Kenotariatan dan Keadaan Memaksa - Bagus Eko Tri Cahyono; Nuzulia Kumala Sari; Moh. Ali (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid development of information technology has driven transformation across various sectors, including notarial practices through digitalization and the concept of cyber notary. However, the existence of electronic deeds within the Indonesian legal system continues to raise issues regarding their legal validity, particularly in relation to the formal requirements for authentic deeds. This study aims to analyze the possibility of executing electronic deeds from the perspective of notarial law and to examine whether force majeure (overmacht), such as the COVID-19 pandemic, can serve as a legal justification for such practices. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that, normatively, electronic deeds are not yet fully accommodated under Law Number 2 of 2014 concerning Notary Position, which still requires the physical presence of the parties before a notary as an essential element of authenticity. Although Law Number 11 of 2008 concerning Electronic Information and Transactions recognizes electronic documents as valid legal evidence, such recognition does not automatically grant electronic deeds the status of authentic deeds within the notarial framework. Furthermore, force majeure conditions such as the COVID-19 pandemic cannot be used as a legal basis to override formal legal requirements, but rather function as a justification for the inability to fulfill certain legal obligations. Therefore, regulatory reform is necessary to accommodate technological advancements while maintaining the principles of prudence and legal certainty in notarial practice, particularly in addressing extraordinary circumstances in the future.